PEMANFAATAN SERESAH DAUN BAMBU (Dendrocalamus asper) SEBAGAI BIOHERBISIDA PENGENDALI GULMA YANG RAMAH LINGKUNGAN - Lutfy Ditya Cahyanti (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2015)
Uncontrolled weed growth in the early stages of crop establishment, can decrease final crop yield. Phytochemical compounds from bamboo’s (Dendrocalamus sasper) leaves known as flavonoids, phenolic and coumarin that inhibit the growth and development of weeds. The objective of this study was to utilizing bamboo’s leaves litter as bioherbicide for sustainable agricultural system. Weedy area used for observation of the effectiveness solution of bamboo’s leaves litter as bioherbicide is 1 m², first area for solution of bamboo’s leaves litter 10%, the second area for solution of bamboo’s leaves litter 5% and third plot only distilled water as a control treatment. Weeds SDR observations was done before spraying and 7 days after spraying bamboo’s leaves litter. The selected plot is a plot with diverse species of weeds. Observations SDR weeds to determine the level of effectiveness of a solution of bamboo’s leaf litter, was conducted used quadrant plots Weed species that dominated on our plot are Mikania micrantha, Eleusine indica, Cyperus rotundus, Cynodon stolon, Cynodon dactylon, Axonopus compressus dan Sanchus arvensis. Solution of bamboo’s leaves litter as bioherbicide are only capable controlled bermuda grass (Cynodon dactylon), both at a dose of 5 % and 10 %. For other species, solution of bamboo’s leaves litter did not work at